Keterlibatan Masyarakat Urban dalam Pengolahan Sampah Rumah Tangga - Yosica Mariana (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Generally, activities conducted by people generate waste. The waste which increasingly rises causing a big problem. Therefore, the role of community in waste management will strongly support the process of solving the waste problem in the community. The purpose of this study was to determine the relationship of engagement and active participation of citizens, as reflected in the attitude of citizens in the activities related to the response to the waste problem in the community. A descriptive method was used in this study to describe the involvement and participation in the prevention of waste. The result showed that the paradigm of PSBM (community-based waste management) appeared sporadically and has not yet received the maximum support from regional governments. A paradigm which is “people pay, the government manages“, has grown within the community for years. It would hardly change people’s behaviour patterns in solving the waste problem in the community since changing the city into a city that is clean, comfortable and healthy involved many parties, including the community.